2008
DOI: 10.1021/bm701037x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of in vitro Calcium Phosphate Mineralization by Combinatorially Selected Hydroxyapatite-Binding Peptides

Abstract: We report selection and characterization of hydroxyapatite-binding heptapeptides from a peptide-phage library and demonstrate the effects of two peptides, with different binding affinities and structural properties, on the mineralization of calcium phosphate mineral. In vitro mineralization studies carried out using one strong- and one weak-binding peptide, HABP1 and HABP2, respectively, revealed that the former exhibited a drastic outcome on mineralization kinetics and particle morphology. Strong-binding pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
166
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(169 citation statements)
references
References 44 publications
1
166
0
2
Order By: Relevance
“…Once this is achieved, peptide-based molecular scaffolds developed may have great potential for applications in tissue regeneration. An example from our recent work on biomineralization using hydroxyapatite (HA)-binding peptides (Gungormus et al 2008; M. Gungormus, D. Khatayevich, C. So, C. Tamerler & M. Sarikaya 2008, unpublished data) is shown in figure 5a,b. We demonstrated that the biocombinatorially selected HA-binding peptides could offer a route for regulating calcium phosphate-based nanocrystal formation within a biomedical context.…”
Section: Implementations Of Solid-binding Peptides In Bionanotechnologymentioning
confidence: 99%
“…Once this is achieved, peptide-based molecular scaffolds developed may have great potential for applications in tissue regeneration. An example from our recent work on biomineralization using hydroxyapatite (HA)-binding peptides (Gungormus et al 2008; M. Gungormus, D. Khatayevich, C. So, C. Tamerler & M. Sarikaya 2008, unpublished data) is shown in figure 5a,b. We demonstrated that the biocombinatorially selected HA-binding peptides could offer a route for regulating calcium phosphate-based nanocrystal formation within a biomedical context.…”
Section: Implementations Of Solid-binding Peptides In Bionanotechnologymentioning
confidence: 99%
“…They could be derived from native proteins having conserved fragments in different organisms or created by artificial evolution (11). Several groups have used artificial evolutionary systems to identify HA-binding peptides (12)(13)(14). On the other hand, natural peptides are mostly fragments of bone tissue proteins that are known to be involved in the mediation of HA formation.…”
mentioning
confidence: 99%
“…11,12 GEPIs have been studied for applications in interface engineering ranging from bionanotechnology 13 to bionanomedicine. 14 The conformation and structure of GEPIs are dependent on their composition and environment. By tuning the pH of its solution, the secondary structure of the peptide can be changed as a result of variation in hydrogen bonding and interaction between residues.…”
mentioning
confidence: 99%